Thermodynamics studies of protein adsorption on PVDF membrane: article - Mohd Rashid, Amirah Asyiqin; Ideris, Norhidayah (2017)
The application PVDF membrane in immunoassays nowadays is significant especially for the use of detecting of contagious disease such as typhoid and many types of influenza. Therefore, the reason of conducting this study is to characterize the Polyvinylidene Fluoride (PVDF) membrane in terms of morphology, polymorph and hydrophobicity by using several methods and equipment which are Field Emission Scanning Electron microscopy (FESEM), Fourier-Transform Infrared Spectroscopy (FTIR), water contact angle using Video Contact Angle system and porosity test. This study is also aimed to investigate the thermodynamic aspect for adsorption of bovine serum albumin (BSA) as a model protein on PVDF membrane